IOT based self-tracking solar powered smart irrigation system - Raheman, Abdul; Kameswara Rao, M; Vamsi Reddy, B; Ravi Kumar, T (International Journal of Engineering and Technology, 2018)
This Article is based on the Agriculture where it is the backbone of our country. This paper mainly deals with monitoring the conditions like soil, water in Agriculture. There are several factors that effects the Agriculture that may be a lack of water facility, and utilization of proper pesticides in proper time, and sometimes due to the low soil moisture content available in the soil. In this paper it discusses the soil and water conditions and how can we supply the proper water with respected to time as well as without the human intervention. For this we need some hardware’s and software’s integrated together for a final output. When going to do this project we need a lot of technologies that must be integrated together such as sensor networks, Cloud computing, big data, and finally some Interfaces to control the things. Here the farmer can supply the water in time to time so it needs a power supply to run the motor for that it is better to take a solar energy because it is a Renewable energy and could supply the energy throughout the day time. And there are some few existing problems that can be analysed. Finally this paper forecasts the monitoring of soil, water conditions in the Agriculture.